De la sémiologie à la sémio-pragmatique, du texte aux espaces mentaux de communication - Roger Odin; Julien Péquignot (Communiquer)
Co-founder of film studies in France, student of Algirdas Julien Greimas and Christian Metz, Roger Odin works from many years on a pioneering heuristic theoretical model, the semio-pragmatic, which stands considering the flipside of the audience’s doxic experience in order to apprehend its operation and issues. The interview questions the theory’s epistemological and institutional groundings as well as some linked issues.